1999
DOI: 10.1089/hyb.1999.18.99
|View full text |Cite
|
Sign up to set email alerts
|

Combined Surgical and Immunotherapeutic Treatment of Patients with Fourth Stage Colon Cancer

Abstract: Sixty-five patients with the fourth stage colon cancer were subjected to the combined surgical and immunotherapy. The following conclusions are made: (1) surgical elimination of the bulk of tumor mass is a necessary prerequisite for effective immunotherapy; (2) vaccination with autological tumor cells accompanied with bacille bilié de Calmette-Guérin (BCG) as the adjuvant and with interleukin-2 as the immunostimulator effectively prevents metastasizing after successful surgery; (3) the vaccine must necessary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Table 1 shows the characteristics of the six trials included in the meta-analysis [16-21]. Three of the six trials reported data for 7 years follow-up, other three studies followed up for 1 year, 5 years and 7.6 years respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the six trials included in the meta-analysis [16-21]. Three of the six trials reported data for 7 years follow-up, other three studies followed up for 1 year, 5 years and 7.6 years respectively.…”
Section: Resultsmentioning
confidence: 99%
“…IL-2 was also used to improve the anti-tumor activity of other forms of immunotherapy [143][144][145][146][147][148][149][150] chemotherapy [151][152][153][154][155][156] and surgery [157][158][159][160][161][162][163].…”
Section: Discussionmentioning
confidence: 99%